UZBEKISTAN’S POLITICAL PARTIES BETWEEN THE GOVERNMENT AND SOCIETY - RABBIMOV, Kamoliddin (CENTRAL ASIA AND THE CAUCASUS, 2007)
Uzbekistan’s official1 political parties have become an important institution in the re-public’s political life, but they function very differently from parties in democratic coun-tries. If we were to make a schematic drawing of Uzbekistan’s political system, the head of state would be in its center as a powerful nucleus, and all the rest—the government, parliament, parties, judicial power, mass media, and society as a whole—would revolve around him, protecting and attending to the country’s leader. Although their proximity to the center (that is, to the nucle-us) and rotation rate around it differ, there is essentially not one political party that would be willing to leave its orbit and exist in free flight or swim against the current, claiming, in so doing,to be creating its own alternative system. This is legitimate, since the nucleus has al-ways feared any deviations in rotation around it,never sparing any resources to increase people’s disposition and sympathy toward it and always confidently applying negative sanctions, that is,punishing those who tried to launch into free flight or go against the grain. There is no doubt that this primarily applied to political parties. The president has always had biased opinions regarding many of the democrat-ic values and institutions, including the opposi-tion, mass meetings, free mass media, political parties, and democracy as a whole. He has never had any particular confidence in society and the above-mentioned institutions, always considered it necessary to keep control over them, and essentially seen them as threats to stability and security, as well as to his power. A vivid expression of the president’s non-confidence in a civil society was his proclamation during the first years of independence of five principles of the transition period. The first of them said: “The state is the main reformer,” which for all intents and purposes entirely contradicted the Constitution of the Republic of Uzbekistan. This principle, which had defined Uzbekistan’s entire era of sovereignty, de facto established anetatist system of statehood and greatly strengthened authoritarianism. The “state is the main reformer "thesis defined the government’s unconditional supremacy with respect to other branches of pow-er and a civil society.